Theoretical Analysis of the Vibrations of the Louvered Surface When Cleaning Cotton from Small Impurities - A. N. Dusmatov; O. Sh. Sarimsakov (Research Parks Publishing LLC, 2023)
In order to increase the cleaning efficiency of the machine in the equipment for cleaning seeded cotton from small impurities, a blind surface is proposed instead of a mesh surface. When choosing the technological parameters of cleaning cotton from small impurities, the main control developments and calculation processes were considered.